New focal mechanisms reveal fragmentation and active subduction of the Antalya slab in the Eastern Mediterranean - Guvercin, Sezim Ezgi; Konca, A. Ozgun; Ozbakir, Ali Deger; Ergintav, Semih; Karabulut, Hayrullah (ELSEVIER, 2021)
In the Eastern Mediterranean, the convergence of Nubia and Eurasia is accommodated along the Hellenic and Cyprus Trenches. The plate geometry and mode of convergence to the east of the Hellenic Trench remains poorly understood. Specifically, along the west of Cyprus, tomography models reveal NW striking high velocity anomaly, which is interpreted as a slab named as the Antalya slab. However, near surface observations pertaining to the top 15 km of the convergence zone show no evidence of an active subduction in the region. In this study, we investigate the seismic activity along the Antalya slab in order to constrain the mode of convergence and the geometry along this plate boundary. Towards this end, we obtain a new focal mechanism catalogue with reliable centroid depths for earthquakes M-w > 4 from regional waveforms by using path dependent seismic velocity models. Our results indicate that the subduction is still active along the plate boundary segment between Cyprus and Anaximander seamount. The earthquakes along the slab interface reveal a NE-dipping slab with a dip angle of similar to 35 degrees. Slip vectors show a pure convergent motion which is consistent with relative motion of Anatolia with respect to Nubia. We also identify a number of intraslab earthquakes down to a depth of 120 km along the Antalya slab. The T-axis of intraslab earthquakes show down-dip extension consistent with negatively buoyant subducting slab. The Paphos fault bounds the Antalya slab to the east where previously large right-lateral earthquakes occurred, which marks the relative motion of the Antalya slab with respect to the eastern Cyprus slab. Based on slab isodepth contours of the slab interface, we calculate similar to 100 km offset between the 80 km depth contours of the Antalya and Cyprus slabs. The western boundary of the Antalya slab possibly lies between the Anaximander and Anaximenes seamounts, where several left-lateral earthquakes are obtained. The western boundary of the Antalya slab can also be identified from orientation change of normal fault earthquakes along overriding plate which shows the limit of N-S extension due to roll-back of the neighboring Hellenic slab.
Keywords: Slab fragmentation; Focal mechanisms; Intraslab stress; Eastern Mediterranean; P-WAVE TOMOGRAPHY; ANAXIMANDER MOUNTAINS; CYPRUS ARCS; EARTHQUAKE MECHANISMS; SOURCE PARAMETERS; MOMENT TENSORS; EVOLUTION; MANTLE; DEFORMATION; LITHOSPHERE; Geochemistry & Geophysics